Is Spending an Additional 5-15 on Each Sample a Good Investment as an Insurance Policy Against Wasting Your Exploration Dollar or Losing a Good Ore Body in your Filing Cabinet? (The Australasian Institute of Mining and Metallurgy, 1986)
What is the real value of your data?Given that the cost of collecting and analysing an individual sample is always rising, it is important to understand the true value of a sample and that you are confident that you receive good value for your exploration dollar. Unfortunately too many samples are still collected today that will end up as worthless data; a liability to those who own it and a hindrance to finding that ore body.